TEAM QUIZ LEARNING ASSISTED BY THE QUIZIZZ APPLICATION: AN EFFORT TO INCREASE STUDENT LEARNING MOTIVATION AT BOJONGLONGOK STATE ELEMENTARY SCHOOL - Dayanty, Agustien Dwi; Hopeman, Teofilus Ardian (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2024)
The purpose of this research is to develop soft skill-based interactive media, to know the quality of This Classroom Action Research aims to describe the increase in learning motivation of class VI-B students at Bojonglongok State Elementary School after learning was implemented as a team quiz with the help of a quiz application. This research is Classroom Action Research, conducted at Bojonglongok State Elementary School, especially in class VI-B with a total of 36 research participants. The results of Classroom Action Research show that the attention indicator for sub-indicator 1 reached 67% in pre-cycle, 97.2% in cycles 1 and 2, while sub-indicator 2 reached 10.1% in pre-cycle, 67 % in cycle 1 and 94.4% in cycle 2. The indicator's relevance reached 17% in the pre-cycle, 75% in cycle 1, and 97.2% in cycle 2. The confidence indicator reached 31% in the pre-cycle -cycle, 67% in cycle 1, and 100% in cycle 2. Finally, the satisfaction indicator reached 10.1% in pre-cycle, 100% in cycle 1, and 86% in cycle 2, which means a decrease of 14% from cycle 1 to cycle 2. However, student learning motivation can be said to have motivation to learn. Thus, it can be concluded that quiz team learning assisted by the quiz application can increase the learning motivation of class VI-B students at Bojonglongok State Elementary School.